Does mental exertion alter maximal muscle activation? - Rozand, Vianney; Pageaux, Benjamin; Marcora, Samuele M.; Papaxanthis, Charalambos; Lepers, Romuald (Frontiers in Human Neuroscience, 2014)
Mental exertion is known to impair endurance performance, but its effects on neuromuscular function remain unclear. The purpose of this study was to test the hypothesis that mental exertion reduces torque and muscle activation during intermittent maximal voluntary contractions of the knee extensors. Ten subjects performed in a randomized order three separate mental exertion conditions lasting 27 minutes each: i) high mental exertion (incongruent Stroop task), ii) moderate mental exertion (congruent Stroop task), iii) low mental exertion (watching a movie). In each condition, mental exertion was combined with ten intermittent maximal voluntary contractions of the knee extensor muscles (one maximal voluntary contraction every 3 minutes). Neuromuscular function was assessed using electrical nerve stimulation. Maximal voluntary torque, maximal muscle activation and other neuromuscular parameters were similar across mental exertion conditions and did not change over time. These findings suggest that mental exertion does not affect neuromuscular function during intermittent maximal voluntary contractions of the knee extensors.